EVALUASI KRIM ANTIOKSIDAN SOLID LIPID MICROPARTICLE EKSTRAK ETANOL DAUN KERSEN (Muntingia calabura) - Amriani Sapra; Radhia Riski; Besse Jamila (Media Kesehatan Politeknik Kesehatan Makassar, 2020)
ABSTRAK Kersen (Muntingia calabura L.) leaves is a plant that contains flavonoids as antioxidants which can be formulated in Solid Lipid Microparticle. The aim of this study is to make Solid Lipid Microparticle cream loaded ethanol extract of kersen leaves preparation and evaluated it’s physical stability. Solid Lipid Microparticle was made of 3% kersen leaves ethanol extract with entrapment efficiency 85.75% formulated in cream preparation with variation of cetyl alcohol concentration namely F1 (2%), F2 (4%), F3 (6%), then tested it’s stability before and after accelerated storage using climatic chamber. The results showed that the three formulas fulfilled the quality of preparation with organoleptic, homogenity, type of cream, viscosity, pH, and spreadability parameters before and after accelerated conditions. Keywords : Kersen leaves, Muntingia calabura L., physical stability, Solid Lipid Microparticle Cream